A new catfish of the genus Silvinicthys (Teleostei: Trichomychteridae) from Leoncito National Park, Argentina - Fernandez Luis (2012)
Silvinichthys leoncitensis, new species, is described from Leoncito National Park in the Andes of Argentina. The new species is distinguished from the other two known congeners by the coloration pattern, consisting of a dark marmorated head and body that fades to a paler color ventrally, the pelvic fin and girdle absent, seven to nine opercular odontodes, 18-28 interopercular odontodes, caudal-fin length 19.9-24.0 % SL, length of dorsal fin base 10.1-13.1 % SL, and head width 13.3-15.9 % SL. Silvinichthys leoncitensis is endemic to the type locality, which is situated in the Andean Cordillera of the San Juan province, Argentina. Silvinichthys leoncitensis is hypothesized to be a sister species of S. bortayro.